Strategi Komunikasi Kelurahan Kalibaru Kecamatan Cilincing Dalam Mengatasi Permukiman Kumuh - Chandra, Salsa Nabilah Septiani; Hakim, Lukmanul; Febriantin, Kariena (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This paper discusses the communication strategies employed by Kalibaru Village, Cilincing Subdistrict, in addressing slum areas. Slum areas in Kalibaru Village are one of the serious problems that impact the quality of life of the community. This research is important to determine the effectiveness of the communication strategies implemented by the local government in improving environmental cleanliness and health. The purpose of this study is to identify the communication strategies implemented by Kalibaru Village and assess their impact on changes in community behavior. This research has broad relevance in terms of social and government policy because the problem of slums reflects social inequality in terms of facilities and infrastructure. This study uses a qualitative approach with a descriptive method, based on Harold Lasswell's communication theory. Data collection techniques were carried out through direct interviews with relevant sources and field observations. Using these methods, the researcher was able to gain an in-depth understanding of the slum area improvement program. The results of the study revealed that although some communities began to understand the importance of waste management and took action to improve cleanliness, overall awareness was still low due to internal factors such as habits and a lack of understanding about waste management. The conclusion of this study is that the communication strategies implemented are quite effective for some communities, but they still need to be improved through more consistent education and active community participation. Based on the research results, it is recommended that the Cilincing Subdistrict improve its participatory communication approach through direct face-to-face interactions and expand the use of digital media.